Holocene climate variations in the western Antarctic Peninsula: evidence for sea ice extent predominantly controlled by changes in insolation and ENSO variability - Etourneau, J.; Collins, L. G.; Willmott, V.; Kim, J.-H.; Barbara, L.; Leventer, A.; Schouten, S.; Sinninghe Damsté, J. S.; Bianchini, A.; Klein, V.; Crosta, X.; Massé, G. (Climate of the Past, 2013)
n/a